2015
DOI: 10.1155/2015/713828
|View full text |Cite
|
Sign up to set email alerts
|

The Changes of Retinal Saturation after Long-Term Tamponade with Silicone Oil

Abstract: Purpose. To evaluate the effects of long-term tamponade with silicone oil on retinal saturation. Methods. A total of 49 eyes that received tamponade with silicone oil were included. The patients were divided into 3 groups (3–6 months, 6–9 months, and >9 months) according to the duration of silicone oil tamponade. Retinal oximetry was performed using the Oxymap system before and 2 months after silicone oil removal. Results. The mean retinal oxygen saturation before silicone oil removal was 107% ± 12% in the art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
0
18
0
2
Order By: Relevance
“…, 2016; Lou et al. ). In the present study, our data showed that 1 week after ICL implantation, oxygen saturation of retinal venules decreased slightly but significantly compared to preoperative measurements, as did the diameter of retinal vessels; otherwise, the oxygen saturation of retinal arterioles was normal.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…, 2016; Lou et al. ). In the present study, our data showed that 1 week after ICL implantation, oxygen saturation of retinal venules decreased slightly but significantly compared to preoperative measurements, as did the diameter of retinal vessels; otherwise, the oxygen saturation of retinal arterioles was normal.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, in Gao's study, decreased retinal oxygen saturation and decreased AV difference as well as narrowing retinal vessel diameter were observed in high myopic eyes, compared with normal subjects (Zheng et al 2015). The variations in retinal oxygen saturation might reflect early microangiopathy, which has been suggested to be correlated with unusual anatomy and physiology changes of the retina, not only in ocular diseases but also in ophthalmic surgery (S ın et al 2014;Lou et al 2015). Currently, whether the ICL implantation surgery would further affect the retinal oxygen saturation of high myopic eyes has not been defined.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, Ma et al (15) reported that for the use of silicone oil for periods of <9 months, silicone oil vesicles were observed only on the surface of the retina, whereas after 9 months, these vesicles began to enter the sensory layer of the retina. Furthermore, the use of SOT for >9 months causes alterations to retinal saturation and narrowing of retinal arterioles, which may further interfere with oxygen metabolism in the retina; no such changes were observed within a tamponade period of ≤9 months (16).…”
Section: Discussionmentioning
confidence: 99%
“…Even though no typical electrophysiological pattern has been found in previous studies, generalized macular dysfunction with retinal lesions of ganglion cells and horizontal-bipolar cell synaptic processes in the outer plexiform layer have been reported as possible mechanisms [ 47 , 58 , 65 , 66 ]. An alternative hypothesis is that SO emulsification and resulting tissue infiltration induces mechanical obstruction of the retinal vasculature and a decrease in retinal oxygen saturation that can trigger retinal hypoxia, particularly on the outer retina layers [ 6 , 50 , 67 , 68 ]. Besides that, other reports state that SO causes oxidative stress, by physical blockage of oxygen and metabolic exchange between the retina and the vitreous humor [ 69 ].…”
Section: Introductionmentioning
confidence: 99%